1997
DOI: 10.1002/(sici)1098-2396(199711)27:3<208::aid-syn7>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease hyperphosphorylated tau aggregates hydrophobically

Abstract: The chemical interaction that condenses the hyperphosphorylated protein tau in Alzheimer's disease (AD P-tau) into neurofibrillary tangles and cripples synaptic transmission remains unknown. Only beta-sheet, positive ion salt bridges between phosphates, and hydrophobic association can create tangles of just AD P-tau. We have correlated transmission electron microscope (TEM) images of tau aggregation with different percentages of beta-sheet in aqueous suspensions of tau while using buffers that block dispositiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The binding between AD P-tau and MAPs seemed to be of hydrophobic nature because it is stimulated at 200 mM NaCl and inhibited at 2 M NaCl; also, it is completely inhibited by Ϸ0.5% Triton X-100 (15,18). AD P-tau can sequester the six isoforms of tau with different affinity; fetal tau binds the least of the six isoforms (19).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The binding between AD P-tau and MAPs seemed to be of hydrophobic nature because it is stimulated at 200 mM NaCl and inhibited at 2 M NaCl; also, it is completely inhibited by Ϸ0.5% Triton X-100 (15,18). AD P-tau can sequester the six isoforms of tau with different affinity; fetal tau binds the least of the six isoforms (19).…”
mentioning
confidence: 64%
“…The portion of tau molecule involved in tau-tau interaction seems to be the microtubule-binding domain (17,19,(37)(38)(39) and of hydrophobic nature (15,18). The involvement of this tau region in the interaction is suggested because the interaction improves when the second microtubule-binding domain (i.e., four-repeat tau) is present (17).…”
Section: Discussionmentioning
confidence: 99%
“…is an unusual protein that has long stretches of charged (positively and negatively) regions that are not conducive for intermolecular hydrophobic association (47). Of the four microtubule binding repeats in , the predicted amino acids having ␤-structure are concentrated in R2 and R3 (33) and can selfassemble into filaments in vitro; R2 and R3 have also been shown to coassemble with heparin into PHF (48).…”
Section: Discussionmentioning
confidence: 99%
“…Although disulfide bonds resistant to cytoplasmic reduction are found in globular proteins, they are not expected in a protein like tau, which is believed to exist in an extended conformation with limited secondary structure (Cleveland et al, 1977b. Since the region of tau that contains the cysteine residues is known to be a relatively hydrophobic part of the molecule (Ruben et al, 1991), however, it is possible that conformational changes associated with dimerization and/or polymerization trap the relevant cysteines in a central hydrophobic domain not easily accessed by reducing agents.…”
Section: Figmentioning
confidence: 99%
“…The average total polymer length/field Ϯ S.E. is plotted as a function of the initial cation concentration, n Ն 10. demonstrated that the secondary structure content of tau also increased as a function of temperature (Ruben et al, 1991). It is likely, therefore, that prior to polymerization the tau molecule assumes a more highly ordered conformation.…”
Section: Figmentioning
confidence: 99%